Adaptation Model of Women Head of Poor Family Facing the Covid-19 Pandemic to Achieving SDGs - Indra Kertati; Susetyo Darmanto; Totok Tumangkar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aimed to formulate a model and analyze the efforts of women heads of low-income families in dealing with the COVID-19 pandemic. The real impact that occurs, especially for women heads of low-income families, is the decline in the household economy, gender vulnerabilities such as limited accessibility, the inability to maintain legal identity, especially for divorced women, a large number of dependents, and the loss of the work they have been working. The question of this research is how the models and efforts of women heads of low-income families adapt to the COVID-19 pandemic. The research method uses a mixed-method, with a locus of Surakarta city, the number of informants interviewed by women heads of low-income families is 41 people, carried out by observation, in-depth interviews, and focus group discussions. The results showed that most of the female heads of poor households could adapt by changing their livelihoods, strengthening and mobilizing family members, making changes to their diet, and increasing social piety. The social environment and local government also support adaptation. The gender cross-cutting approach found issues related to community empowerment, women's empowerment and child protection, and small and medium business cooperatives.